The influence of transformational leadership, talent management, and organizational culture on change management in the international non-profit organization - Mailangkay, Merry Mersia Gristie; Ardi, Ardi; Sunarjo, Richard Andre (Enrichment : Journal of Management, 2024)
Transformational leadership suggests that inspiring and motivating leaders are more likely to facilitate successful organizational change. Talent management emphasizes the importance of attracting, developing, and retaining skilled individuals during change. Organizational culture, representing shared values and practices, also plays a crucial role in shaping employee attitudes towards change. The Objective of this study to analyse the influence of transformational leadership, talent management, and organizational culture on change management in international non-profit organizations XYZ in Indonesia. This research methodology employs a quantitative approach by using a questionnaire distributed to 36 respondents consisting of managers and employees in the international nonprofit organization XYZ in Indonesia. The collected data will be analysed using the PLS-SEM method to test the relationship between the independent variables (transformational leadership, talent management, and organizational culture) and the dependent variable (change management). The findings of this study highlight the importance of talent management and organizational culture in driving change management within international non-profit organizations in Indonesia, while also indicating that transformational leadership does not significantly impact change management. This research provides valuable insights for practitioners and managers on the importance of inspirational and motivational leaders who involve employees in decision-making and leverage their skills, while also building a flexible and adaptive organizational culture to effectively manage complex changes